Tendensi kesalahan berbahasa jawa pada materi pranatacara siswa kelas X SMA N 1 Karanganyar Kabupaten Kebumen - Oktavia Puspita Dewi; Nur Hanifah Insani (Aksara: Jurnal Bahasa dan Sastra, 2023)
Pranatacara as one of the Javanese subjects has numerous benefits for students in social life, including in Kebumen Regency. Unfortunately, students frequently make language errors in maximizing their pranatacara speaking abilities, which are influenced by a region's dialect, with the ngapak dialect in Kebumen district being the subject of this research. The gap in this study lies in the difference of the pranatacara's notion where a pranatacara requires the usage of archaic language but the data generated uses krama inggil language. This study attempts to analyze phonological and morphological errors in class X students' instructional material in pranatacara practice. This research employs descriptive qualitative methods and research validation techniques to extend observations and enhance perseverance. The examination information was as hands-on practice results from 36 class X students of SMA N 1 Karanganyar, Kebumen. Data examination was finished by data decline and the results were then explained using an error investigation table. In this review, it was discovered that error in the pronunciation of the vowel "a," which transformed to the vowel "o," predominated linguistic errors in phonology and morphology. The phonological errors included the words menopo, kulo, soho, etc. while morphological errors are in the form of monggo, saengga, pramila, and other. According to studyâ€™s findings, it can be seen that a significant population in Kebumen still unable to utilize Javanese properly and correctly. Regional languages may lose their viability as a result. By conducting research, people will hopefully become more conscious of the need of preserving their native language by starting to speak using a variety of krama properly and correctly according to their regional accent.Â Keywords: language errors, phonology, morphology, pranatacara, Ngapak dialect